Relevance of polymorphisms in MC4R and BDNF in short normal stature - Nikolas Herrfurth; Anna-Lena Volckmar; Triinu Peters; Gunnar Kleinau; Anne Müller; Cigdem Cetindag; Laura Schonnop; Manuel Föcker; Astrid Dempfle; Stefan A. Wudy; Struan F. A. Grant; Thomas Reinehr; et al. (BMC, 2018)
Abstract Background Variation in genes of the leptinergic-melanocortinergic system influence both body weight and height. Because short normal stature (SNS) is characterized by reduced body height, delayed maturation and leanness, allelic variation of genes in this pathway are hypothesized to affect this common condition. Methods We analyzed the coding regions of LEP, MC4R, MRAP2 and BDNF in 185 children with SNS (height < 5th percentile) to search for non-synonymous and frameshift variants. For association studies (two-sided χ2-tests) population-based data sets (ExAC, EVS and KORA) were used. Cyclic AMP accumulation, cell surface expression, central expression and MAP kinase activation were assayed in vitro to determine the functional implications of identified variants. Results We detected eleven variants predicted to be protein-altering, four in MC4R, four in BDNF, and three in MRAP2. No variants were found in LEP. In vitro analysis implied reduced function for the MC4R variant p.Met215Ile. Loss-of-function is contrary to expectations based on obesity studies, and thus does not support that this variant is relevant for SNS. The minor SNP alleles at MC4R p.Val103Ile and BDNF p.Val66Met were nominally associated with SNS. Conclusion Taken together, although genes of the leptinergic-melanocortinergic system are important for normal growth, our data do not support the involvement of rare mutations in LEP, MC4R, MRAP2 or BDNF in short normal stature.